KARAKTERISTIK KEWIRAUSAHAAN MASYARAKAT DALAM USAHA KOPI BUBUK DI DESA KOTO TUO KECAMATAN SUNGAI TARAB KOTA BATUSANGKAR SUMATERA BARAT - Monika, Tri Cici; Wilson, Wilson; Maemunaty, Titi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The formulation of problem in this research is "How is the adjective entrepreneurial aspect of the business in coffee powder business in Koto Tuo Village Tarab River District Batusangkar West Sumatera". This research uses descriptive naturalistic research with qualitative approach which aims to give the right picture about the Characteristic of Community Entrepreneurship in Coffee Powder Business in Koto Tuo Village Sungai Tarab District Batusangkar City, West Sumatera. This research consist of one variable that is with research indicator that is (1) Have a strong desire to stand alone, (2) Have willingness to take risk, (3) Have ability to learn from experience, (4) Able to motivate self, 5) Have the spirit to compete, (6) Have a relationship with hard work (7) Have great confidence. The subjects of this study were 5 informants ie 1 core informant, 2 control informants, and 2 informant observers. Technique of data collection is by using, interview, and documentation. Based on the results of interviews with informants, the researchers found the data through the 7 indicators is clear that the types of jobs that exist in the Village Koto tuo Tarab River District Batusangkar West Sumatra City is the equipment used to process coffee powder that is the furnace and parikiran engine in create your own. How the sale is done by going down directly to the surface and have some merchandise. The most superior here is to have children who use coffee with a very large number and will sell back to customers who have been looking for. The more children the more coffee powder sold. It remains consistent to the packaging of ground coffee, because from the first establishment of this business only disposable packaging but still with the same brand. Keywords: Characteristics, Entrepreneurship, Community, Coffee Powder Business.